Imagining and Enacting Liberatory Pedagogical Praxis in a Politically Divisive Era. Issue 2 (3rd July 2019) - Wilson, Camille M.; Hanna, Margaret O.; Li, Michelle
ABSTRACT: In this essay, the authors challenge the myth of political neutrality in teaching and emphasize the urgent need for teachers to imagine and enact liberatory pedagogical praxis that sensitively responds to the nation's divisive political climate. They point to U.S. political shifts and changing federal policies in education as catalysts for the social and cultural exclusion of vulnerable children of color. They suggest how teacher educators and in-service teachers can use media sources that reveal how children experience and navigate increasingly xenophobic and polarizing political climates as critical texts. Critical pedagogy and civic education scholarship offer frames to further explain how such texts serve to enhance students' learning, sense of belonging, and their ability to contribute to a democratic and just society. The authors conclude with strategies for supporting teachers' development and advocacy.